A Note on Block Tariffs - Gabor, Andre (Review of Economic Studies, 1955)
Journal Article A Note on Block Tariffs Get access Andre Gabor Andre Gabor Nottingham Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 1, 1955, Pages 32–41, https://doi.org/10.2307/2296149 Published: 01 April 1955